THE 3KAT APPROACH: TRANSFORMING SELLING COSTS AND PRICES DETERMINATION CAPABILITY - Mohamad Ghaffar , Affizah; Kamisan , Faezah; Khazali , Siti Hajar (Journal of Islamic, Social, Economics and Development, 2024)
Governing the correct cost and price is paramount in business management but is often neglected and causes the business to go bankrupt. The Click Cost Cash Flow Calculator (3KAT) is a mobile access application designed and developed for cost, price determination, and business cash flow preparation. The 3KAT project is an application dedicated to aiding enterprises in quickly and easily calculating expenses and determining selling prices. 3KAT was developed to micro-entrepreneurs, overcome financial and accounting issues and to provide a solution for them to easily record their business transactions and all the costs associated with the production of their products to determine the correct selling price. Product costs and prices, as well as cash flow, can be generated automatically, removing the need for manual computation or writing on paper, both of which are prone to loss. If the cost of business supplies and expenses fluctuates, it can be used frequently to determine costs and prices. Additionally, receipt and expense reports can be generated at a time of your choosing. 3KAT was built with an AppSheet app based on the ADDIE model that includes 5 phases which is the analysis phase, design, development, implementation, and evaluation phase. The 3KAT gives value-added competency to entrepreneurs in the costing and pricing process which impacts acceptance, adjective, grade, percentile rank, and promoter and detractor in the evaluation of System Usability Scale (SUS) score. The implications of this study show that the adoption of the 3KAT mobile application provides positive potential from the aspect of usability and its use on users with an average SUS score of 81.5 by 60 micro-entrepreneurs. Thus, 3KAT is able to give great impact and benefits to users who are involved in business, especially those who do not have an accounting background.